Perancangan Penyiraman Kandang Berbasis Arduino Uno Guna Menjaga Stabulitas Suhu dan Kelembapan - Octavian, Muhammad Wirawan; Mundari, Siti (Jurnal Teknik Industri Terintegrasi (JUTIN), 2024)
In the poultry farming industry, chicken coops are very important. The air temperature in the chicken coop is one of the environmental components that has a big influence on the welfare and productivity of chickens. Temperature control in the chicken coop is very important to maintain optimal health and performance of livestock because excessive air temperature can cause heat stress, which can be detrimental to health, comfort and productivity of chickens. Value Engineering (VE) is a systematic approach used in project management, product design, construction, or business processes to increase the value of a product or process by optimizing the ratio between quality and cost. The total cost of making an Arduino Uno microcontroller is 495,500 and requires a power capacity of 10.81 Watts with a total annual maintenance cost of 166,665. The costs required to run the Arduino and water pump for 24 hours in one month are around IDR 13,963.35. And from this research, it is concluded that using an Arduino Uno-based sprayer is more affordable and more efficient in using the tool. It can be seen that the monthlycostreachesIDR.221,721